Makna Simbolik Alat Musik Gamelan Yogyakarta bagi Generasi Muda - Fuad Mudzakir; Zayid Zidane Aulia; Zulfa Nadin Azzahra; Nazwa Rizky Adilla; Naila Fadlia; Syairul Bahar; Farkhan Abdurochim Alfarauq (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to examine how the young generation of Yogyakarta interprets gamelan as part of their cultural identity amid the dynamics of modernity. Using a descriptive qualitative approach, data were obtained through document analysis and in-depth interviews with an informant closely connected to the gamelan tradition. The findings show that young people’s interpretation of gamelan emerges through four main dimensions: material, spiritual, social, and aesthetic. In the material aspect, gamelan is understood as an ancestral heritage born from traditional crafting processes rich in values of hard work and local wisdom. In the spiritual dimension, rituals such as fasting, offerings, and the bathing of instruments are viewed as symbols of human connectedness with Javanese cosmological values. Socially, gamelan functions as a space for togetherness and as a marker of cultural identity that strengthens the younger generation’s ties to their traditional roots. Meanwhile, in the context of modernity, gamelan is reinterpreted through contemporary musical collaborations, karawitan education, and the use of digital technology. The study’s findings affirm that gamelan remains a living and meaningful cultural symbol, and its continuity is strongly influenced by how young people embody and interpret the tradition in their daily lives.